Načelo enakosti in pozitivna diskriminacija v pravnem urejanju položaja manjšin - Klopčič, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Author elaborates on the hypothesis that the concept of equaliity and positive discrimination within the frame of protection of national or ethnic minorities has a specific connotation. It is reflected in the fact that the territorial principle prevails within the concept of guarantees; because of the historical background minority rights were originally established as an independent system and only recently incorporated within the wider frame of the international human right protection. In the article some cases from the case law from the European Court of Human Rights and cases from the Slovenia are quoted which prove that the evolution in the field of protection of minorities at international level is still not adequately represented in the internal regulation of obligations of States to adopt positive measures for improvement of the position of vulnerable groups in individual states. Quoted cases from Slovenia prove its determination to continue with measures of "positive discrimination" in the line of the guarantees stated in the Constitution of the Republic of Slovenia for two constitutionally recognized national minorities and Roma community in Slovenia, on the basis of territorial principle. The Framework Convention for the Protection of National Minorities also opensa door for the development of the protection of other minority groups in Slovenia and for application of a more flexible approach to the adoption of special measures for their participation in publiclife, as well as for maintenance of their identity, culture and language.
Keywords: narodne manjšine; človekove pravice; human rights; pozitivna diskriminacija; varstvo manjšin; zaščita manjšin